Description of two new species of sea bass (Teleostei: Latidae: Lates) from Myanmar and Sri Lanka - Pethiyagoda, Rohan; Gill, Anthony C. (Zootaxa, 2012)
Two new species of Lates Cuvier are described. Lates lakdiva, new species, from western Sri Lanka, differs from its Indo-Pacific congeners by its lesser body depth, 26.6‒27.6% SL; 5 rows of scales in transverse line between base of third dorsal-fin spine and lateral line; 31‒34 serrae on the posterior edge of the preoperculum; third anal-fin spine longer than second;47‒52 lateral-line scales on body; and greatest depth of maxilla less than eye diameter. Lates uwisara, new species, fromeastern Myanmar, is distinguished by possessing 7 scales in transverse line between base of third dorsal-fin spine and lat-eral line; eye diameter 4.4‒4.7% SL; body depth 28.4‒34.5% SL; and third anal-fin spine shorter than the second. Despitesubstantial genetic variation, L. calcarifer sensu lato is widely distributed, from tropical Australia through Indonesia, Sin-gapore and Thailand, westwards to at least the west coast of India. Caution is urged in translocating Lates in the Indo-Pacific region as other yet unrecognized species likely exist. The status of the type specimens of L. calcarifer is discussed,and a common lectotype designated for L. heptadactylus and L. nobilis. While Lates vacti (type locality Bengal) may bea valid species, L. cavifrons and L. darwiniensis are considered synonyms of L. calcarifer. Plectopomus Goldfuss and Ptertopomus Goldfuss are shown to be incorrect subsequent spellings of Plectropomus Oken.